Kleopatra i Dydona - antyteza ideału kobiety czasów Augusta = Cleopatra and Dido as an antithesis of Roman woman's ideal in the time of Augustus - Dutkiewicz, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The ideal of a Roman woman differed substantially from the mythical image of Dido the queen of Carthage as well as the conduct of Cleopatra the queen of Egypt. Both Vergil and Plutarch describing Dido or Cleopatra did not criticise directly the women lifestyles. Nonetheless, they did emphasize in their detailed descriptions their improper behaviour which for the reader of that time was explicitly blameworthy.
Keywords: Kleopatra VII; Dydona